Corporate Dividends and Seasoned Equity Issues: An Empirical Investigation. - Loderer, Claudio F; Mauer, David C (Journal of Finance, 1992)
This paper investigates whether managers rely on dividends to obtain a higher price in a stock offering and whether the stock price reaction to dividend and offering announcements justifies such a coordination. The evidence does not support either conjecture. Issuing firms are not more likely to pay or increase dividends than nonissuing firms. Moreover, there is little evidence that firms time stock-offering announcements right after dividend declarations to benefit from the attendant information disclosure. The analysis of dividend and stock-offering announcement effects suggests few if any benefits from linking dividend and stock-offering announcements.